ANALISIS YURIDIS PERKAWINAN YANG TIDAK DICATATKAN PADA LEMBAGA PENCATAT PERKAWINAN - Wahyudi Sulistia Nugroho (Jurnal ADIL, 2019)
he Law No.1/1974 clearly stipulates that marriage must be registered at theregister office or at religious affairs office. Still, there are people who ignore it; theylet their marriage be unregistered. Although unregistered marriage is essentiallyaccepted from the religious aspect since it has met all the religious terms andrequirements, it is legally unjustifiable because it is not registered to the civilmarriage registrar. What has then become an issue is that the number ofunregistered marriages is significantly growing so that the couples do not haveauthentic evidence which is an essential document for the legal security of theirmarriage. An unregistered marriage unquestionably brings legal consequences tothe status of the couples (the husband and the wife), the status of their children, aswell as the status of their estate. There are many factors which contribute to thephenomenon of unregistered marriages.